Freeware. (Economist, 1992)
The article reports that a Californian software company called Cygnus Support Inc. gives products away for nothing, with no restrictions on their reproduction. The company specialises in software tools for computer programmers, one of the fastest-changing segments of a highly competitive industry. Though its products are free, Cygnus charges $300 an hour to tailor its programmes to a customer's specific needs. Cygnus reserves the right to include any of the modifications it makes for customers in its free products.